37 ARE TICS IN FRAGILE X SYNDROME RELATED TO AUTISM?. Issue 1 (1st January 2007) - Wirojanan, J.; Yuhas, J.; Harris, S.; Cook, K.; Goodlin-Jones, B. L.; Ono, M.; Hagerman, R. J.
Abstract : Objective: To determine the correlation between tics and autism in patients with fragile X syndrome (FXS). Method: Medical records of patients with FXS ages 5 and older were reviewed. Autism and pervasive developmental disorder (PDD-NOS) were diagnosed by a team of developmental pediatricians and psychologists after a thorough assessment, which included the Autism Diagnostic Observation Schedule (ADOS) and/or Autism Diagnostic Interview-Revised (ADI-R). Results: One hundred forty-one patients, 106 males (78.7%) and 35 females (21.3%) between the ages of 5 and 42 years old (10.9 years ± 5.7), were included. History of motor and/or vocal tics or Tourette syndrome (TS) was found in 25 patients (17.7%), 21 males and 4 females. Nineteen of those patients (76%) also had autistic spectrum disorder (ASD) (either PDD-NOS or autism), which was higher than the prevalence of ASD in patients with FXS who did not have tics or TS (76% vs 50.9%, p = .022). This association was found significant among females (75% vs 12.9%, p = .019) but not in males (76.2% vs 64.7%, p = .316). Conclusions: These preliminary results suggest a significant association between tics and autism in females with FXS. Perhaps the additional genetic load related to tics is additive to the full mutation in females to increase the risk of autism.